Alkylation of benzene with alpha-olefins over zirconia supported 12-silicotungstic acid - Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
Liquid phase alkylation of benzene to linear alkyl benzene (LAB) with alpha-olefins has been investigated with 12-silicotungstic acid supported on zirconia (STA/ZrO2) as the catalyst. Among the catalysts, 15 wt.% STA/ZrO2 calcined at 750 degrees C was found to be most active than others in the alkylation reaction. The total amount of acid sites of different STA loaded catalysts were estimated by TPD of NH3 and 15 wt.% STA/ZrO2 calcined at 750 degrees C was found to have the highest acidity and more active in the reaction. The optimization of reaction conditions of alkylation of benzene with 1-dodecene was performed with 15 wt.% STA/ZrO2 calcined at 750 degrees C by varying catalyst concentration (1-5 wt.% of reaction mixture); temperature, 373-423 K and benzene: 1-dodecene (1-dd) molar ratio, 5-15 in a Parr autoclave under N-2 pressure. Under the optimized reaction conditions, conversion of 1-dodecene (50.8%) gave high selectivity to 2-phenyl dodecane (47.1%) and the remaining 3-, 4-, 5- and 6-phenyldodecanes in 4 h. The reaction was found to be heterogeneously catalyzed and no contribution from homogeneous (leached) STA into the reaction medium. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1-dodecene; 12-silicotungstic acid; Alkylation; Benzene; LAB; Zirconia

Benzylation of benzene and other aromatics by benzyl chloride over mesoporous AlSBA-15 catalysts - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hartmann, Martin; Halligudi, Shivappa B. (Microporous and Mesoporous Materials, 2005)
Aluminum-containing mesoporous molecular sieves AISBA-15 with different n(Si)/n(Al), ratios and AIMCM-41 have been synthesized hydrothermally and characterized in detail by physicochemical methods, viz. XRD, N(2) adsorption and (27)Al NMR spectroscopy. The low angle XRD and N2 adsorption measurements reveal that the structural order of SBA-15 was retained after the incorporation of Al. The increase of the unit cell parameter with increasing aluminum content and (27)Al MAS NMR spectroscopy confirm the incorporation of aluminum in the framework. Benzylation of benzene and substituted benzenes reaction employing benzyl chloride as the alkylating agent over AISBA-15 and AIMCM-41 have been investigated. The influence of various reaction parameters such as reaction temperature, reactant feed ratio and catalyst amount affecting the activity and selectivity of AISBA-15, have been studied. Among the mesoporous catalysts studied, AISBA-15(45), where the number in parentheses indicates the molar nsilnA, ratio, shows both high conversion and high selectivity for the benzylation of benzene. The activity of this catalyst for the benzylation of different aromatic compounds is in the following order: benzene > toluene > p-xylene > mesitylene > anisole. Kinetics of the benzene benzylation over different catalysts have also been investigated. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Alkylation; AlSBA-15; Benzylation; SBA-15

Liquid-phase alkylation of phenol with long-chain olefins over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The liquid-phase alkylation of phenol with 1-dodecene was carried out over WOx/ZrO2 solid acid catalysts. The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO3 was calcined from 700-850 degrees C. All the catalysts were characterized by surface area, XRD, and FTIR. The catalyst with 15% WO3 calcined at 800 degrees C (15 WZ-800) was found to be the most active in the reaction. The effect of temperature, molar ratio and catalyst weight on dodecene conversion and products selectivity was studied in detail. Under the optimized reaction conditions of 120 degrees C, phenol/1-dodecene molar ratio 2 and time 2 h, the catalyst 15 WZ-800 gave > 99% dodecene conversion with 90% dodecylphenol selectivity. Comparison of the catalytic activity of 15 WZ-800 with sulfated zirconia calcined at 500 degrees C (SZ-500) and HP zeolite showed that activity of SZ-500 was lower than that of 15 WZ-800, while HP zeolite showed negligible activity. It is observed that the presence of water in the reaction mixture was detrimental to the catalytic activity of WOx/ZrO2. The catalyst 15 WZ-800 also found to be an efficient catalyst for alkylation of phenol with long-chain olefins like 1-octene and 1-decene. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Alkylation; long-chain olefins; phenol; tungsten oxide; Zirconia

Stereoselective syntheses of (+)-alpha- and (-)-beta-conhydrine from L-aspartic acid - Pandey, SK; Kumar, P (Tetrahedron Letters, 2005)
An efficient synthesis of (+)-alpha-conhydrine 1 and (-)-beta-conhydrine 2 has been achieved by. diastereo selective alkylation of an amino aldehyde derivative 7 with ethylmagnesium bromide or diethylzinc. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkylation; conhydrine; Grignard reaction; Piperidine alkaloids; stereoselectivity

Synthesis of poly(1-hexene)s end-functionalized with phenols - Yanjarappa, Mallinamadugu J.; Sivaram, Swaminathan (Polymer International, 2005)
Electrophilic alkylations of phenol/2,6-dimethylphenol were performed with vinylidene-terminated poly(1-hexene)s using BF3-OEt2 catalyst. Vinylidene-terminated poly(1-hexene)s with M. varying from 400 to 10000 were prepared by bulk polymerization of 1-hexene at 50 to -20 degrees C using Cp2ZrCl2/MAO catalysts. The phenol/2,6-dimethylphenol-terminated poly(1-hexene)s was characterized by NMR (H-1, C-13), UV, IR and vapor phase osmometer (VPO). The isomer distribution (ortho, para and ortholpara) was determined by P-13 NMR using a phosphitylating reagent, namely 2-chloro-1,3,2-dioxaphospholane. The number-average degree of functionality (F-n) > 0.9 with > 95% para selectivity could be achieved using low-molecular-weight oligomers of poly(1-hexene)s. (c) 2005 Society of Chemical Industry.
Keywords: Alkylation; chain-end functionalization; functional poly(olefin)s; metallocene catalysts

Effect of calcination temperature on the catalytic activity of zirconia-supported heteropoly acids - Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Zirconia-supported silicotungstic acid (15% STA) catalyst with different calcination temperatures (600-850 degrees C) was prepared by suspending zirconium oxyhydroxide in methanol solution of STA followed by drying and calcination. These catalysts were characterized by XRD, FTIR pyridine adsorption and DRUV-vis spectroscopy. The catalysts showed both Bronsted as well as Lewis acidity and 15% STA on zirconia calcined at 750 degrees C (15 SZ-750) had the highest Bronsted acidity. Characterization of 15 SZ-750 catalyst by Raman spectroscopy showed the presence of zirconia-anchored mono-oxotungstate as the major tungsten species present in this catalyst. These catalysts were used in benzoylation of veratrole with benzoic anhydride and 15 SZ-750 catalyst showed the highest activity. For catalyst with support calcined at different temperatures before HPA impregnation, catalytic activity decreases as the support calcination temperature increases due to the decrease in Bronsted acidity. Comparison of the catalytic activity of 15 SZ-750 with that of zirconia-supported phosphotungstic acid (15%, calcined at 750 degrees C, 15 PZ-750) in benzoylation of veratrole with benzoic anhydride, acylation of anisole with acetic anhydride and in alkylation of diphenylether with 1-dodecene showed that 15 SZ-750 catalyst has higher activity and deactivation resistance due to its higher Bronsted acidity. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Alkylation; Anisole; diphenylether; Phosphotungstic acid; Silicotungstic acid; veratrole; Zirconia

Heteropoly acid supported on titania as solid acid catalyst in alkylation of p-cresol with tert-butanol - Kumbar, Suresh M.; Shanbhag, G. V.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Butylation of p-cresol with tert-butanol was investigated on titania modified with 12-tungstophosphoric acid (TPA/TiO2) catalyst under vapor phase conditions. Catalysts with different TPA loadings (10-25 wt.%) and calcination temperatures (650-750 degrees C) were prepared by suspending titanium hydroxide in methanol solution of TPA followed by drying and calcination. These catalysts were characterized by surface area, XRD, P-31 MAS NMR, XPS, NH3-TPD, and FTIR pyridine adsorption. XRD results indicated that the presence of TPA retarded the crystallization of titania and stabilized TiO2 in anatase phase. P-31 MAS NMR indicated the presence of TPA in various forms (dispersed, highly fragmented and Keggin intact). These catalysts showed both Bronsted and Lewis acidity, and 20% TPA on TiO2 calcined at 700 degrees C (from here after words 20% TT 700) had the highest Bronsted as well as total acidity. Further, the catalytic activities were examined in tert-butylation of p-cresol with tent-butanol. The catalytic activity depended on TPA coverage, and the highest activity corresponded to the monolayer of TPA on titania. The most active catalyst 20% TT-700 gave 82% conversion of p-cresol and 89.5% selectivity towards 2-tert-butyl cresol (TBC), 2,6-di-tert-butyl cresol (DTBC) 7.5% and cresol-tert-butyl ether (CTBE) 3% under optimized conditions. The activity was always higher than that of WO3/ZrO2, sulfated zirconia (SZ), USY, H-beta zeolites and montmorillonite K-10 (K-10mont) under similar conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2; 2-tert-butyl-p-cresol; 6-di-tert-butyl-p-cresol; Alkylation; heteropoly acid; p-Cresol; tert-butanol; titania

Liquid phase alkylation of phenol with 1-octene over large pore zeolites - Wagholikar, Smita; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2006)
A comparative study is presented of the liquid phase alkylation of phenol with 1-octene over different zeolite catalysts: H-beta (BEA(15)), H-mordenite (MOR(11)) and H-USY (FAU(15)). A wide spectrum of monoalkylated products, identified as isomers of phenyl octyl ether (O-alkylate) and octyl phenol (C-alkylate), was formed in the reaction. The reaction was studied in detail over BEA(15), such studies included the influence of process variables such as temperature, reactant mole ratio, catalyst amount and alkali metal (K) poisoning on its performance in the alkylation reaction. A kinetic analysis of the reaction over BEA(15) was also carried out assuming a second order parallel reaction mechanism. The activity of the different catalysts for the reaction followed the order: BEA(15) > FAU(15) > MOR(11). The poisoning of BEA(15) with potassium resulted in a decrease in the catalyst activity concomitant with a decrease in the number of strong acid centres in the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 1-octene; alkyl phenols; Alkylation; phenol; zeolites

Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

Synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates using Na-Y zeolite catalyst - Shivarkar, Anandkumar B.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synlett, 2006)
A simple, efficient, and environmentally benign methodology for the synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates in the presence of the highly active and reusable solid base catalyst Na-Y zeolite is demonstrated.
Keywords: Alkylation; alkylene carbonate; Amine; Amino alcohols; zeolite

Efficient and practical total synthesis of (+/-)-alpha-cuparenone - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthesis-Stuttgart, 2007)
A one-pot cyclopentannulation approach as the key step for the total synthesis of (+/-)-alpha-cuparenone is described.
Keywords: Alkylation; annulation; hydroboration-oxidation; reduction

Heteropolyacid supported on acidic clay: a novel efficient catalyst for alkylation of ethylbenzene with dilute ethanol to diethylbenzene in presence of C-8 aromatics - Bokade, Vijay V.; Yadav, Ganapati D. (Journal of Molecular Catalysis A-Chemical, 2008)
Vapor phase alkylation of ethylbenzene with ethanol to diethylbenzene is industrially relevant. Diethylbenzene is an important raw material for the conversion of divinyl benzene monomer. Conventionally, it is prepared from diacetophenone by reduction. It is also prepared by vapor phase alkylation of ethylbenzene with ethylene using zeolitic catalysts. The efficacy of dodecatungsotphosphoric acid (DTPA) supported on acid treated clay has been evaluated in the current work in the alkylation of ethylbenzene with 80% (w/w) ethanol. 15% (w/w) DTPA/K-10 clay was found to be an efficient and robust catalyst. The use of aqueous ethanol and a mixed C-8 stream lowers the cost of production. A kinetic model is developed by studying the important process parameters with 15% (w/w) DTPA/K-10 as the catalyst. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkylation; diethylbenzene; Heteropolyacid; kinetics; Solid acids

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Selective N-alkylation of aniline with methanol over a heteropolyacid on montmorillonite K10 - Nehate, Manoj; Bokade, Vijay V. (Applied Clay Science, 2009)
N-methylaniline is an industrially important product in the manufacture of paper, textile dyes, drugs, perfumes and explosives. The vapour phase alkylation of aniline with methanol forming N-methylaniline is advantageous over liquid phase alkylation. In present study, vapour phase methylation of aniline over dodecatungestophosphoric acid supported on K10 montmorillonite was systematically studied and optimization of process parameters was carried out. The 20% m/m DTPA/K10 was found to be optimum with 79% aniline conversion and 99% N-methylaniline selectivity. The reaction required milder operating conditions than reported for commercial catalysts. We also studied the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of aniline with other alcohols like ethanol, n-propanol, iso-propanol and n-butanol. The activity of 20% m/m DTPA/K10 decreased with increasing carbon number. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkylation; Aniline; Heteropolyacid; montmorillonite K10; N-methylaniline

Orthogonally protected cyclohexanehexols by a ``one reaction - one product'' approach: efficient access to cyclitols and their analogs - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
Differentially protected myo-inositol derivatives were prepared from commercially available myo-inositol through regioselective O-alkylation reactions, which give a single product in each step. These derivatives were converted into six isomeric inositol derivatives carrying orthogonal hydroxy protecting groups. For all these reactions, conditions were chosen to prevent the formation of isomeric products, which obviates the need for separation of isomers and provides the required cyclitol derivative in very good yields. The synthetic potential of these derivatives was illustrated by the conversion of some of the orthogonally protected inositol derivatives into other cyclitol derivatives. Isomeric inositols were also prepared by the global deprotection of all the hydroxy groups.
Keywords: Alkylation; cyclitols; Inositol; Protecting groups; Regioselectivity

Alkylation of anisole with 1-hexene and 1-hexanol over zeolite H-beta - Surse, P. V.; Wagholikar, S.; Mayadevi, S.; Sivasanker, S. (Reaction Kinetics Mechanisms and Catalysis, 2011)
An examination of the kinetics of the alkylation of anisole with 1-hexene and 1-hexanol to produce alkylates over zeolite H-beta is presented. Anisole alkylation is found to occur by a set of parallel reactions when hexene is used as the alkylating agent. When hexyl alcohol is the alkylating agent, the reaction follows a multi-step parallel-series mechanism to form monoalkylates and dihexylether. With 1-hexene, a group of isomeric alkylates, viz., ortho-2-hexyl anisole (2-OHA), ortho-3-hexyl anisole (3-OHA), para-2-hexyl anisole (2-PHA), and para-3-hexyl anisole (3-PHA) was obtained. With hexanol, the olefin (hexene) and dihexyl ether were obtained additionally. The influence of process parameters like temperature, catalyst quantity, and alkylating agent on reaction behavior is reported.
Keywords: Alkylation; Anisole; H-beta; Hexene; Hexyl alcohol

Alkylation of benzene to cumene over mor zeolite catalysts - Vyawahare, Yogesh K.; Chumbhale, Vilas R.; Aswar, Anand S. (Revue Roumaine De Chimie, 2012)
The vapor phase alkylation of benzene to cumene (isopropyl benzene) is studied over MOR (mordenite) type zeolite at different process parameters. The reaction was also studied by adopting different methodologies (pyridine poisoning, passing of moist propylene, alkali dominant mordenite, use of coked catalyst and metal impregnated zeolite) to check the nature of product distribution and the extent of activity and selectivity to alkylated product IPB, DIPB (isopropyl benzene and diisopropyl benzene) and n-PB (n-propyl benzene). It is revealed that the adoption of different methodologies affects the activity and selectivity significantly by suppressing of alkylation / isomerisation reactions.
Keywords: Alkylation; cumene; isopropanol; MOR zeolite; propylene

Reactions in supercritical carbon dioxide - Mayadevi, S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Use of conventional organic solvents often leads to the formation of hazardous waste, the disposal of which is a matter of environmental concern. Carbon dioxide is considered to be a green reaction medium and a good replacement for conventional organic solvents as it is benign and leads to elimination/reduction of hazardous wastes. Use of CO2 at near/above critical conditions has several additional advantages as the reactions can be pressure-tuned to eliminate transport resistance, increase solvent power and heat capacity. Hence, there has been considerable interest in the use of supercritical carbon dioxide as either a replacement of conventional organic solvent or as a co-solvent in reactions. Herein, recent developmenst in this area during the last decade is reviewed, specifically in gas-liquid (organic hydrogenation, hydroformylation and oxidation) and liquid-liquid (carbon-carbon coupling, alkylation, acetylation, esterification) reactions.
Keywords: Alkylation; Carbon dioxide; Hydroformylation; Hydrogenation; Oxidation; Supercritical carbon dioxide

Modular synthesis of dihydroxyacetone monoalkyl ethers and isosteric 1-hydroxy-2-alkanones - Gueclue, Deniz; Rale, Madhura; Fessner, Wolf-Dieter (European Journal of Organic Chemistry, 2015)
Straightforward methods for the efficient, systematic preparation of libraries of the title compound classes have been evaluated. A general and efficient modular route to dihydroxyacetone monoethers was developed based on trityl glycidol, which, through epoxide opening, oxidation, and deprotection, provided variously alkylated ethers by three routine operations in good overall yields (eight examples, 24-59%). The preparation of structurally related 1-hydroxyalkanones depends on the availability of the most economic starting materials and on their physicochemical properties. Thus, the most practical one-step approaches consisted of the sec-selective oxidation of short-chain 1,2-diols (<= C-6) using NaOCl, and the direct ketohydroxylation of 1-alkenes (>= C-6) using buffered stoichiometric KMnO4 or catalytic RuO4 with reoxidation by oxone, for which mostly good overall yields were achieved on a multigram scale (nine examples, 15-78%).
Keywords: Alkylation; Hydroxylation; Ketones; Oxidation; Oxygenation; Regioselectivity; synthetic methods

Effect of donors on the activation mechanism in ziegler-natta catalysis: a computational study - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (Chemcatchem, 2016)
Full quantum chemical calculations, using density functional theory (DFT), have been conducted to explain the effect of donors on the ``activation mechanism'' in the Ziegler-Natta (Z-N) catalyst system. In the activation mechanism, the inactive (TiCl4)-Cl-IV catalyst converts into the active (TiCl2Et)-Cl-III catalyst with the help of the AlEt3 present in the system. The donors that have been considered in this study are: ethyl benzoate (eb), two representative diether cases, a phthalate donor, and a silyl ester donor. The results indicate that eb and the diether donor cases donor have a negative effect on the barriers for the activation mechanism. However, the eb donor can be displaced from the MgCl2 surface by AlEt3, which matches experimental observations. For the phthalate, silyl ester and TiCl3-OC4H8Cl cases, the results indicate that a significant induction period would be present in Z-N systems employing such donors or having such a catalytic center, before catalysis could commence.
Keywords: Alkylation; aluminum; Density functional calculations; surface chemistry; titanium

Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations

Nickel-catalyzed N-vinylation of heteroaromatic amines via C-H bond activation - Landge, Vinod G.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2017)
Here, we report a ligand- and reductant-free nickel-catalyzed N-vinylation of heteroaromatic amines using biorenewable p-cymene as a solvent. This unprecedented cross-coupling strategy has high functional group tolerance (halides, alkoxy, cyano, chiral motif, etc.) and proceeded via C-H bond activation.
Keywords: Alkylation; Amination Reactions; Anilines; Aryl Chlorides; halides; Monoarylation; O Bonds; Precatalyst; Pyrimidines; Removeble Directing Group

Synthesis and characterization of six-membered pincer nickelacycles and application in alkylation of benzothiazole - Pandiri, H.; Sharma, D.M.; Gonnade, R.G.; Punji, B. (Journal of Chemical Sciences, 2017)
Six-membered pincer nickelacycle complexes have been synthesized and employed for the catalytic C–H bond alkylation of benzothiazole. The pincer nickelacycle, {κP, κC, κP- (2 - iPr 2POCH 2-C 6H 3- 6 -CH 2OP iPr 2)} NiBr , [(iPr4-POCCCOP)NiBr(2)] was synthesized by the reaction of 1,3 - iPr 2POCH 2-C 6H 4-CH 2OP iPr 2[(iPr4-POCCCOP)-H(1)] with (CH3CN)2NiBr2 in the presence of Et 3N via the C(2)–H activation on ligand 1. Treatment of [(iPr4-POCCCOP)NiBr](2) with AgOAc afforded the complex [(iPr 4-POCCCOP) Ni (OAc)] (3) in good yield. Both the complexes 2 and 3 were characterized by 1H , 13C and 31P -NMR spectral analysis. Further, the molecular structures of complexes 2 and 3 were established by X-ray crystallography. The complex 2 was found to be an active catalyst for the C–H bond alkylation of benzothiazole with alkyl halides containing β–hydrogen atoms. Graphical abstract: Synopsis. Six-membered pincer nickelacycles have been synthesized and structurally characterized, which show catalytic activity for the C–H bond alkylation of benzothiazole with alkyl halides containing β–hydrogen atoms.[Figure not available: see fulltext.].
Keywords: Active catalyst; Alkyl halides; Alkylation; Atoms; Benzothiazole; Benzothiazoles; Catalyst activity; Chemical activation; Crystallography; C–H activation; Hydrogen atoms; Nickelacycles; Pincer complex; Pincer complexessix-membered nickelacycle; six-membered nickelacycle; Spectrum analysis; Synthesis (chemical); Synthesis and characterizations; X ray crystallography

Altering the O/C ratio of lignin derived monomers without sacrificing atom efficiency - Singh, Dheerendra; Dhepe, Paresh L. (ChemistrySelect, 2019)
Synthesis of platform and fuel grade chemicals from lignin without losing atom efficiency and lowering O/C ratio is a challenge in a bio-refinery concept. In this work, we report solid acid catalysed alkylation of lignin derived variety of monomers such as guaiacol, veretrole, phenol, anisole, and catechol using numerous alcohols as alkylating agents. Results elaborate that the type of acidity and structure of catalyst play important role in achieving higher dialkylated products (DAP). With 85% conversion of guaiacol, 30.9% DAP formation was achieved at 250 degrees C within 2 h. A unique substrate adsorption study on the catalyst surface and effect of solubility of substrates on the activity of catalyst is evaluated. Catalyst was observed to be recyclable with marginal loss in the activity due to handling error.
Keywords: Alcohols; Alkylation; lignin; Monomers; solid acid catalyst; Up-gradation

Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides

Manganese-catalyzed C(sp(2))-H alkylation of indolines and arenes with unactivated alkyl bromides - Verma, Suryadev K.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Selective C(sp(2))-H bond alkylation of indoline, carbazole and (2-pyridinyl)arenes with unactivated alkyl bromides is achieved using MnBr2 catalyst in the absence of an external ligand. The alkylation uses a simple LiHMDS base and avoids the necessity of Grignard reagent, unlike other Mn-catalyzed C-H functionalization. This reaction proceeded either through a five- or a less-favored six-membered metallacycle, and tolerated diverse functionalities, including alkenyl, alkynyl, silyl, aryl ether, pyrrolyl, indolyl, carbazolyl and alkyl bearing fatty alcohol and polycyclic-steroid moieties. Alkylation follows a single electron transfer (SET) pathway involving 1e oxidative addition of alkyl bromide and a rate-limiting C-H metalation.
Keywords: Alkylation; C-H activation; indoline; ligand-free; manganese

Revisiting classical pummerer cyclization reaction: a key strategy for the synthesis of (+/-)-quinagolide - Chavan, Subhash P.; Kawale, Sanket A.; Tripathi, Anupam; Kadam, Appasaheb L.; Gonnade, Rajesh G. (ChemistrySelect, 2022)
A formal synthesis of (+/-)-quinagolide using beta-alanine as a starting material has been achieved. Late stage intramolecular classical Pummerer reaction has been used as a key synthetic tool to construct octahydrobenzo[g]quinoline skeleton of quinagolide. Conjugative reduction of olefin, regioselective C-alkylation over O-alkylation of beta-ketoester followed by retro-Dieckmann/ Dieckmann reaction sequence has been used as a key reaction sequence to achieve prerequisite sulfoxide for the Pummerer reaction. While revisiting the classical Pummerer reaction, the one-pot sequential thionium ion induced cyclocarbamation followed by N-carbamate deprotection and Friedel-Crafts type Pummerer cyclization was observed as an important finding of the present work.
Keywords: Alkylation; Cyclocarbamation; Hyperprolactinemia; rearrangement; Thionium ion

Advances in the iron-catalyzed direct functionalizations of heterocycles - Pradhan, Chandini; Punji, Benudhar (Synlett, 2023)
Direct functionalization of heterocycles is an advanced strategy for diversifying privileged and biorelevant heterocycle-containing molecules. Particularly, use of the most abundant transition metal, iron, as a catalyst makes this process highly cost-effective and sustainable. Recently, some progress has been realized towards the direct functionalization of heterocycles under iron catalysis. Herein, we present the developments in the C-H bond functionalizations and related reactions of various heterocycles by abundant iron salts. This Synpacts is categorized into different sections based on heterocycles being functionalized, and each section is discussed based on the type of reaction catalyzed by iron. 1 Introduction 2 Functionalization of Indoles 2.1 Alkylation 2.2 Alkenylation 2.3 Other Reactions 3 Oxindoles and isatins 3.1 C-C Bond Formation 3.2 C-Heteroatom Bond Formation 4 Pyridines and Furans 5 Functionalization of Azoles 6 Summary and Outlook
Keywords: Alkylation; azoles; C-H functionalization; heterocycles; indoles; iron; Mechanism

Nickel-catalyzed branch-selective C-H alkylation of indoles and azoles with alkenes: an additive- and solvent-free approach - Ankade, Shidheshwar B.; Banerjee, Shuvajit; Punji, Benudhar (European Journal of Organic Chemistry, 2024)
The development of sustainable protocols for the synthesis of alkylated heteroarenes is crucial owing to their widespread existence in medicinally relevant and bioactive natural products. Herein, we describe an efficient, additive- and solvent-free approach for the regioselective C-H alkylation of indoles and azoles with alkenes using a nickel catalyst, which proceeds through a chelation-assistance strategy. The reaction exclusively provided branched alkylated products with the compatibility of alkyl, alkoxy, fluoro, trifluoromethyl, alkene, cyano, ester, and carbonyl groups. This protocol is applicable to other heteroarenes, such as imidazoles and benzimidazoles, providing the desired alkylated products with exclusive Markovnikov selectivity. The synthetic utility and scale-up of the reaction are demonstrated, and the protocol is in concord with the principles of green chemistry. Alkylation proceeds through facile and reversible C-H nickelation and alkene insertion processes, presumably involving rate-limiting reductive elimination. A straightforward nickel-catalyzed protocol for the C-H alkylation of indoles and azoles is disclosed that proceeds under additive- and solvent-free conditions. The reaction utilizes readily available alkenes as alkylating partners and delivers Markovnikov products with tolerance of sensitive functionalities. image
Keywords: Alkylation; branch selectivity; indoles; Nickel; solvent-free synthesis

Strategies employing transition-metal free conditions for C-C bond formation in indoles - Ghodake, Balaji M.; Paul, Sayantan; Bhattacharya, Asish K. (ChemistrySelect, 2024)
Indole motifs are omnipresent in nature and can be found in many natural products as well as pharmaceuticals. It is for this reason synthetic transformations of indole have become a topic of interest for the organic and medicinal chemist community for decades. In this review, we have emphasized the functionalization of indoles via transition-metal-free approaches. This review touches on many aspects in different sub-sections, which gives a proposition of the tactics employed for the functionalization of indoles and an overview of the road ahead. In this review, essentially transition-metal-free conditions for C-C bond formation reactions in indoles has been explored. This review describes various approaches of functionalization at the C-2, C-3, C-4 and C-7 position of indoles which comprises arylation, alkenylation, acylation, formylation, alkylation, bisindolyl and cyclization strategies. Also, strategies incorporating N-alkylation/arylation has also been covered. image
Keywords: Alkylation; Arylation; formylation; Indole; transition-metal free